Development of Android Media in Learning Islamic Religious Education and Character by Believing in Allah's Books for Class VIII Students - Mustagfirin Mustagfirin; Achmad Munib; Aris Abdul Ghoni; Sumardi Sumardi (Universitas Wahid Hasyim, 2024)
A communication tool and source of information in learning, one of which is the use of Learning Media. This requires careful teacher position in selecting the use of media in the educational process to be able to increase student motivation in learning with the benefits of learning, namely: 1) the educational process becomes more interesting, 2) the learning process becomes more efficient and effective, 3) saves energy and time . In reality, in Islamic Religion and Character lessons with the material of Believing in Allah's Books, students often experience difficulties in learning this knowledge. Difficulties faced by students in studying Islamic Religion and Character lessons with the material of Believing in Allah's Books. Based on the results of surveys and observations at SMPN 2 Dempet Demak, it was revealed that the main challenges faced by students regarding understanding the material